Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Di PT Bess Finance Cabang Bandung - Toto Sugiarto (Program Studi Manajemen, Universitas Al Ghifari, 2019)
Employees are a valuable corporate asset that must be managed by the company in order to provide optimal contribution. One of the things that should be the primary concern of the company is the job satisfaction of their employees, because the employees in the work they do not feel comfortable, under-appreciated, can not develop all their potential, then automatically the employee unable to focus and concentrate fully on the job . that the motivation to be a very important part of the underlying individual or someone in doing something or achieve the desired purpose.Salary given to employees company PT Bess Finance so varies according to the position of each. Then the opportunity for career selection to a higher level, reward program for high performing employees. But in certain cases it is also still found a contradictory conditions, which, if observed, would also be potentially lethal even lower motivation.Based on the background above, the research on the effect of motivation on employee performance in PT Bess Finance, this study takes its object to employees of PT Bess Finance located in Bandung. The independent variable (X) is the motivation to work while the dependent variable (Y) is the performance of the employees. This type of research uses explanatory survey, and the method used is Simple Random Sampling, with a total sample 45 respondents. In addition, research is conducted in a timeframe of less than one year of the study using cross-sectional methods. The data used are primary and secondary data and data analysis techniques using statistical parametric application using Spearman rank analysis.These results indicate that the effect of motivation on employee performance indicates a moderate correlation and significant correlation coefficient of 0.477. therefore, the suggestion for the Company Bess Finance to pay attention to in terms of work motivation mnghasilkan employees so that they can work effectively and efficiently.Keywords: Work Motivation and Employee Performance